The Impact of Prosocial Behavior on Well-being and Life Satisfaction - Safiullah Aziz; Razia Khan; Ethan Tan; Zahrotul Uyun (Research Psychologie, Orientation et Conseil, 2025)
Prosocial behavior voluntary actions intended to benefit others is a cornerstone of functional societies. While its benefits for the recipient are clear, a growing body of research in positive psychology suggests that engaging in altruistic acts may also be a powerful and often overlooked pathway to enhancing the actor’s own psychological well-being and overall life satisfaction. This study aimed to empirically investigate the relationship between the frequency of engaging in prosocial behavior and self-reported levels of psychological well-being and life satisfaction in a diverse adult population, and to determine if this relationship holds after controlling for key demographic variables. A cross-sectional survey design was employed with a sample of 450 adults (aged 25-65). Participants completed a battery of validated instruments, including the Prosocialness Scale, the PERMA Well-being Profiler, and the Satisfaction with Life Scale (SWLS). A strong, positive correlation was found between prosocial behavior and both well-being (r = .51, p < .001) and life satisfaction (r = .48, p < .001). The regression analysis revealed that prosocial behavior remained a significant and unique predictor of both outcomes even after controlling for all demographic variables. It accounted for a substantial portion of the variance in both well-being and life satisfaction scores. Engaging in prosocial behavior is a robust and significant predictor of higher psychological well-being and greater life satisfaction. The findings suggest that altruistic actions are not merely a consequence of happiness but are an active ingredient in creating a fulfilling life.